Annual review of working conditions in the EU 2007-2008 - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2008)
The fifth annual review of the European Working Conditions Observatory (EWCO), which is part of the European Foundation for the Improvement of Living and Working Conditions (Eurofound) summarises the main developments at EU level in the area of working conditions and quality of work and employment during the period January to December 2007. The analysis follows the paper Quality of work and employment in Europe: Issues and challenges, compiled by Eurofound (2002), which identifies four key dimensions necessary for the promotion of quality of work: • ensuring career and employment security; • maintaining and promoting the health and well-being of workers; • developing skills and competences; • reconciling working and non-working life.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Labor supply -- European Union countries; Electronic books